Demographic profiles of contact lens wearers and their association with lens wear characteristics in Trinidad and Tobago: A retrospective study. - Ngozika E Ezinne; Dipesh Bhattarai; Kingsley K Ekemiri; Gabrielle N Harbajan; Anesha C Crooks; Khathutshelo P Mashige; Alex A Ilechie; Ferial M Zeried; Uchechukwu L Osuagwu (PLoS ONE)
Purpose Contact lenses (CL) remain a popular mode of refractive error correction globally and in the Caribbean, mostly among young people. However, no data on the characteristics of the CL population wearers in the Caribbean is available. This study reported on the characteristics of CL wearers and the associated factors in Trinidad and Tobago (T&T). Methods This retrospective study reviewed the clinical records of 243 CL wearers who attended the University of the West Indies (UWI) optometry clinic between 2017 and 2018. Data on their demographic profiles, CL wearing characteristics including lens type, material, purpose of wear, replacement schedule and lens care systems were extracted and analyzed. The associations between the demographic characteristics and CL wearing characteristics were also determined. Results About half of the CL wearers used them for fashion (more among those aged 18 to 30 years, 61.0%), therapeutic (more among those <18 years, 43.8%, P = 0.001) and refractive error correction purposes (more in those >40 years, P = 0.001). Females were more likely to use CLs for fashion compared with males (67.0% versus 40.7%). Age (P<0.0005) and gender (P = 0.030) were associated with the lens materials. Those aged 18-30 years were more likely use hydrogels compared with the younger ones (64.1% versus 25.0%). Rigid gas permeable (RGP) CL use was more common in males than females (21.8% versus 10.9%, P = 0.031). Daily disposables were predominantly used by younger respondents (18-30 years old, 31.3%, P < 0.001) and more in females than males (66.7% vs 49.4%, P = 0.040). Conclusion The study found that the CL appears to be more commonly worn for fashion in younger females and for refractive error correction in older males. Age, gender, and employment status were the main determinants of lens wear among respondents attending the university clinic in T&T.